Social and emotional aspects in the climacteric: diagnosis and treatment. - Rondón, Marta B. (2015)
Emotional distress during perimenopause cannot be accounted for only by hormonal fluctuations. Actually, these emotional problems arise from the complex interaction of biological, social and psychological events that coincide in this period of life. The experience of menopause, understood as the end of reproductive life, is influenced by previous psychological growth, which determines how the woman will deal with the challenges of adulthood, namely the loss of some functions and the need to make a balance of expectations and achievements, in order to widen the repertoire of coping strategies in order to face ageing successfully. Role transitions (children leaving home or returning, illness of parents or spouse, changes in the workplace, loss of support networks) impact on emotional well being as do the culturally determined conceptions about menopause of the woman and those around her. Overvaluing youth (equivalent to beauty), glorification of maternity, devaluation of the traditional knowledge of older women and the false idea that death follows shortly after menopause, increase distress and may, in vulnerable women with a previous history of depression, originate a clinical episode of depression which must be properly evaluated and treated.